Effect of tramadol on lung injury induced by skeletal muscle ischemia-reperfusion: an experimental study - Takhtfooladi, Mohammad Ashrafzadeh (Sociedade Brasileira de Pneumologia e Tisiologia, 2013)

(untitled)
OBJECTIVE: To determine whether tramadol has a protective effect against lung injury induced by skeletal muscle ischemia-reperfusion. METHODS: Twenty Wistar male rats were allocated to one of two groups: ischemia-reperfusion (IR) and ischemia-reperfusion + tramadol (IR+T). The animals were anesthetized with intramuscular injections of ketamine and xylazine (50 mg/kg and 10 mg/kg, respectively). All of the animals underwent 2-h ischemia by occlusion of the femoral artery and 24-h reperfusion. Prior to the occlusion of the femoral artery, 250 IU heparin were administered via the jugular vein in order to prevent clotting. The rats in the IR+T group were treated with tramadol (20 mg/kg i.v.) immediately before reperfusion. After the reperfusion period, the animals were euthanized with pentobarbital (300 mg/kg i.p.), the lungs were carefully removed, and specimens were properly prepared for histopathological and biochemical studies. RESULTS: Myeloperoxidase activity and nitric oxide levels were significantly higher in the IR group than in the IR+T group (p = 0.001 for both). Histological abnormalities, such as intra-alveolar edema, intra-alveolar hemorrhage, and neutrophil infiltration, were significantly more common in the IR group than in the IR+T group. CONCLUSIONS: On the basis of our histological and biochemical findings, we conclude that tramadol prevents lung tissue injury after skeletal muscle ischemia-reperfusion.